First report of the Aphis craccivora Koch on Catasetum sp. in Brazil - Leite, Douglas Machado; Garlet, Juliana; Karsburg, Isane Vera (EntomoBrasilis, 2017)
Abstract. The genus Catasetum (Orchidaceae) currently has 194 orchid species distributed throughout Central America, northern Argentina, and southern Brazil, with Brazil as the largest producer with 103 species that may be epiphytic, terrestrial, or rupicolous. Aphids are insect pests that can damage ornamental plants such as orchids, either directly by sucking their sap or indirectly via secretions. Their secretions are attractive to pathogens and other insects, which then feed on the plant and cause a loss of flowers and leaves, spots to appear, reduced flower production, and flowering deformation. These defects can then reduce the value of the plant. When an aphid attack occurs, their ability to rapidly multiply and spread can cause major disruptions to disruptions to parts of the plant’s life cycle. In this report, we examine how the aphid Aphis craccivora Koch infests Catasetum sp. and causes tissue death, decay of the buttons and base of the stem, and stains in the flowers. Thus, owing to the damage that insects of the family Aphididae can cause ornamental plants, this study aims to report the first recorded A. craccivora attack on Catasetum sp. in Brazil. Primeiro relato de Aphis craccivora Koch in Catasetum sp. no Brasil Resumo. O gênero Catasetum (Orchidaceae) tem atualmente 194 espécies de orquídeas distribuídas por toda a América Central, norte da Argentina e sul do Brasil, sendo o Brasil o maior produtor com 103 espécies que podem ser epífitas, terrestres ou rupícolas. Afídeos são insetos-praga que podem danificar plantas ornamentais, como orquídeas, diretamente sugando sua seiva ou indiretamente via secreções. Suas secreções são atrativas para patógenos e outros insetos, que então se alimentam da planta e causam danos em flores e folhas, com surgimento de manchas e deformações nas flores. Estes danos podem então reduzir o valor comercial da planta. Quando ocorre um ataque de pulgão, sua capacidade de se multiplicar e disseminar rapidamente pode causar grandes danos no ciclo de vida da planta. Neste trabalho, relata-se o ataque do pulgão Aphis craccivora Koch em Catasetum sp. O dano observado foi morte de tecidos, e deterioração dos botões e da base da haste, e manchas nas flores. Assim, devido ao dano que os insetos da família Aphididae podem causar plantas ornamentais, este estudo tem como objetivo relatar o primeiro ataque de A. craccivora em Catasetum sp. no Brasil.